TINJAUAN PELAYANAN PELEPASAN INFORMASI MEDIS DAN PENGISIAN BERKAS KLAIM JASA RAHARJA PADA KORBAN KECELAKAAN LALU LINTAS DI RSUD AL-IHSAN KABUPATEN BANDUNG PROVINSI JAWA BARAT - Monica, Rizqy Dimas; Vinandiani, Vina; Hakim, Luqmanul; Hada, Encep; Gunawan, Edih; Rohaeni, Neni (UPPM Politeknik TEDC Bandung, 2024)
This study is entitled Review of Medical Information Release Services and Filling in Raharja Service Claim Files for Traffic Accident Victims at Al Ihsan Hospital, Bandung Regency, West Java Province. The purpose of this study is to determine the Medical Information Release Service and Filling in Jasa Raharja Claim Files for Traffic Accident Victims at Al Ihsan Hospital, Bandung Regency, West Java Province. The method used in this study is: using a descriptive method with a qualitative approach. The subject of this study is the Medical Information Release Service and Filling in the Raharja Service Claim File at Al-Ihsan Hospital, Bandung Regency, West Java Province. The object of this study is the standard operating procedure for releasing medical information and Jasa Raharja claim forms for traffic accident victims who claim Jasa Raharja insurance at RSUD AlIhsan Bandung Regency. Data collection techniques by observation, interview and documentation. Research results: medical information release services at Al-Ihsan Hospital are in accordance with SOPs. There is no written procedure for filling Jasa Raharja's claim file but the implementation is in accordance with the SOP.